The strange case of 'Ugo Fantozzi robot': Control and resistance through comics in a bank. (July 2021) - Carollo, Luca
In this article, I examine a graphic novel created by the management of a banking company and periodically circulated through the company's intranet as part of a training initiative directed at several tens of thousands of employees working at the branch level. Theoretically, my study draws on two main streams of literature: that on Human Resource Management systems as meaning-creating devices to govern the employment relationship and that on the ever-tighter relation between popular culture and organizations. In addition, I elaborate on Umberto Eco's semiotic theory—which to date has been largely overlooked in organization studies—to decipher the 'mystery' represented by the organizational comics case, along with the individual and collective reactions that followed it. On the basis of the available empirical material, I theorize 'Semiological Guerrilla Warfare' as a collective strategy to subvert organizations' internal mass communications. In the final part of the article, I discuss the innovative possibilities that Semiological Guerrilla Warfare, comic strips, and Eco's semiotics offer to organization studies and to all those interested in expanding the repertoire of resistance strategies to managerial control in organizations.